The hospital and clinic improvement handbook : using lean and the theory of constraints for better healthcare delivery / Boʻaz Ronen; Joseph S Pliskin; Shimeon Pass - Ronen, Boʻaz
Includes bibliographical references (pages 267-269) and index.